Tinjauan tentang Ruang Lingkup dan Alat Ukur Tindak Pemerintahan yang Baik - Nasution, Bahder Johan (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2006)
As executive institution a government is restricted by both written and unwritten regulations as bases in all actions. These regulations were used as standards to evaluate all government policies which are stipulated by the government. On the other sides, the government policies are also restricted by the authority derived from delegations, attributions, and mandates. Kata kunci: Hukum Tertulis, Hukum Tidak Tertulis, Alat Ukur, Tindak Pemerintahan yang baik